GAMBARAN PELAPORAN 10 BESAR PENYAKIT (LB1) MENGGUNAKAN GOOGLE DATA STUDIO DI PUSKESMAS - Ari Sukawan; Naida Salsabila (Politeknik Kesehatan Kemenkes Malang (State Health Polytechnic of Malang), 2022)
The Integrated Health Center Recording and Reporting System (SP2TP) is the activity and reporting of general data, facilities, personnel and health service efforts in the community. Reporting is still not fully implemented, but reporting is carried out if the health department requests monthly reporting. The purpose of this study was to find out the description of the reporting of the top 10 diseases (LB1) using Google data studio at the Puskesmas. Subjects and Method: This type of research will use a quantitative with a descriptive research design. The population used is all data on patient visits in September 2021-februari 2022. Results: Monthly reporting using the Google Data Studio application is an alternative solution that can be used by Puskesmas to produce informative dashboards. The presentation of the top 10 disease reports in the form of an online-based dashboard that can be updated automatically by the system so that there will be no data errors or final results errors. The connected data will assist reporting officers in sending reports to the health office. The dashboard of the top 10 disease reports can provide easier and more informative information regarding the highest disease in the Puskesmas every month. Conclusion: Data that is connected to the dashboard, reporting officers are very helpful in sending reports to the online-based health office and speeding up making decisions. Keywords: Recording and Reporting, SP2TP, LB1 , Top 10 Diseases, Google Data Studio